Dalin Dictionary - Base Material - Språkbanken Text (University of Gothenburg, 2024)
Dalin's Dictionary of 19th century Swedish - base material

Dalins ordbok - Ordbok över 1800-talsspråket - basmaterial
Dalin Ordbok Öfver Svenska Språket - basmaterial
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik